"Kebangkitan sebagai Manifestasi Kuasa Allah: Pendekatan Historis-Kritis terhadap Matius 22:23-33 dalam Kontras Keyakinan Yudaisme Reformasi dan Kristen" - Tambun, Roy Haries Ifraldo (Jurnal Teologi dan Pelayanan Kerusso, 2024)
This study aims to analyze the concept of resurrection in Christian and Reform Judaism beliefs, emphasizing that resurrection is a manifestation of God's power over life and death. The study contrasts the Christian belief, which regards resurrection as an integral part of faith, with the Reform Judaism view, which generally rejects resurrection as a literal fact. Using the Historical-Critical interpretation method and a qualitative approach, this research analyzes Matthew 22:23-33 through inner-text and inter-text approaches to reveal its theological meaning and context. The findings show that resurrection is not merely a theological doctrine in the Christian faith, but also serves as evidence of God's power over life and death, aligning with the belief that those who die in faith in God will be resurrected. In conclusion, this research makes a significant contribution to the theological understanding of resurrection, highlights its distinction from Reform Judaism beliefs, and reinforces the role of resurrection as a key element in Christian faith.